(Des)identificações femininas no mosaico de Nélida Piñon - Oliveira, Dileane Fagundes de (2017)
In this work we propose to build a mosaic of feminine characters in some short stories by Nelida Piñon to understand their representation. In so doing, the following narratives were selected : ‘I Love My Husband’, published in O Cortejo do Divino e outros contos escolhidos ( 2007); ‘Colheita’, in Sala de Armas (1997); ‘Aventura de Saber’, ‘Breve flor’ and ‘Os Selvagens da Terra, published in O Tempo das Frutas (1997) and ‘A Camisa do Marido’, found in the book that receives the same title (2014). The analysis attempts to reveal certain aspects related to the patriarchal cultural system of values, specially those about gender relationship, historical and social practices that have interfered in those relations along the centuries. We tried to understand the way Piñon’s subversive writing contributes to deconstruct and denaturalize discourses and practices that, by indulging with Patriarchy, have legitimized both the hierarchical and dualist power relations between the masculine and the feminine genders and the regulations of social roles. As regards the historical, feminine trajectory, the theoretical foundation provided by Simone de Beauvoir, Céli Regina Jardim Pinto, Constância Lima Duarte, Heloísa Buarque de Hollanda, Nelly Novaes Coelho among others, was of high relevance to this research. To reflect upon questions of gender and feminist developments, we resorted to the concepts by Joan Scott, Judith Butler and Teresa de Lauretis that helped to sediment the analysis of the stories. In order to emphasize certain aesthetic aspects related to Piñon’s writing, we researched the studies by Lucia Osana Zolin and Nomi Hoki Moniz, as well as the writer’s own considerations about her work. Along this study, we observed the author’s compromise with a feminine literature: her texts preserve a recurrent dialogue with some of the discussions led by the feminist segments as they attempt to unfold the traditional and stereotyped mechanisms about women through a discourse that is ironic, inquisitive and defiant. Such an investigation allows us to verify the way the author constructs a remarkable variety of female protagonists whose profiles keep a distance - in a higher or lower degree - from the traditional woman portrayal.